1298Associations of DMT therapies with COVID-19 severity in multiple sclerosis. (2nd September 2021) - Simpson-Yap, Steve; Brouwer, Edward De; Kalincik, Tomas; Rijke, Nick; Hillert, Jan; Walton, Clare; Edan, Gilles; Spelman, Tim; Geyes, Lotte; Parciak, Tina; Gautrais, Clément; Lazovski, Nikola; et al.
Abstract: Background: People with multiple sclerosis (MS) are a vulnerable group for severe COVID-19, particularly those taking immunosuppressive disease-modifying therapies (DMTs). We examined the characteristics of COVID-19 severity in an international sample of people with MS. Methods: Data from 12 data-sources in 28 countries were aggregated (sources could include patients from 1-12 countries). Demographic (age, sex), clinical (MS phenotype, disability), and DMT (untreated, alemtuzumab, cladribine, dimethyl-fumarate, glatiramer-acetate, interferon, natalizumab, ocrelizumab, rituximab, siponimod, other) covariates were queried, alongside COVID-19 hospitalisation, admission to ICU, requiring artificial ventilation, and death. Characteristics of outcomes were assessed in patients with suspected/confirmed COVID-19 using multilevel mixed-effects logistic regression, adjusted for age, sex, MS phenotype, and EDSS. Results: 657 (28.1%) with suspected and 1, 683 (61.9%) with confirmed COVID-19 were analysed. Among suspected+confirmed/confirmed-only COVID-19, 20.9%/26.9% were hospitalised, 5.4%/7.2% were admitted to ICU, 4.1%/5.4% required artificial ventilation, and 3.2%/3.9% died. Older age, progressive MS-phenotype, and higher disability were associated with worse COVID-19 outcomes. Compared to dimethyl-fumarate, ocrelizumab and rituximab were associated with hospitalisation (aOR=1.56, 95%CI=1.01-2.41; aOR=2.43, 95%CI=1.48-4.02) and ICU admission (aOR=2.30, 95%CI=0.98-5.39; aOR=3.93, 95%CI=1.56-9.89), though only rituximab was associated with higher risk of artificial ventilation (aOR=4.00, 95%CI=1.54-10.39). Importantly, associations persisted on restriction to confirmed COVID-19 cases. No associations were observed between DMTs and death. Conclusions: Despite the cross-sectional design of this study, the internal and external consistency of these results with prior studies suggests their use may be a risk factor for more severe COVID-19. Key messages: Anti-CD20 DMTs may be associated with worse COVID-19 severity amongst people with multiple sclerosis.